The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

L'autre moitié de l'avant-garde: 1910-1940: femmes peintres et femmes sculpteurs dans les mouvements d'avant-garde historiques - Vergine, Lea (Des Femmes, 1982)
L'autre moitié de l'avant-garde, 1910-1940 est une importante exposition qui s'est tenue à Milan au printemps 1980, puis à Rome, Venise, Amsterdam, Stockholm. D'une rare qualité, elle a remis à jour les démarches et recherches qui, dans la période féconde des années 1930, ont été fondamentales pour l'élaboration d'un langage contemporain. « Préparer ce travail a été, pour moi, une découverte continue : quinze mois passés à chercher dans les caves des musées, à faire ouvrir aux artistes leurs tiroirs. Rares sont les oeuvres que j'ai trouvées accrochées à un mur ! [...] L'exposition évoque les années du Blaue Reiter, du cubisme, du futurisme, du dadaïsme, du Bauhaus. Je voulais voir si les femmes avaient eu ou non, dans ces groupes, la possibilité d'être des forces motrices. Et j'ai découvert, par exemple, que dans l'avant-garde russe, les femmes ont eu un rôle tout à fait décisif...» L.V. Le catalogue rassemble ces monographies, largement illustrées des productions des femmes peintres et sculptrices, et retrace ces mouvements novateurs.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques